Dynamics of Hajj Financial Management regulation in Efforts to Good Governance - Muhammad Aziz Zakiruddin (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2021)
Hajj financial management, especially within the scope of the Ummah Endowment Fund, has a dark record that must be corrected. Not only limited to investment, but the discourse of Hajj funds for infrastructure is also one of the government’s efforts so that Hajj funds can provide use-value. Legal certainty, justice, equality, prohibition of acting arbitrarily, and creating welfare and social cohesiveness in society are the principles of good governance. In Indonesia, to establish an orderly organization of Hajj, laws and regulations, government regulations, presidential regulations, and regulations for the Hajj Financial Management Agency have been made. As for the formulation of the problem in this paper, how are the dynamics of the financial management of Indonesian Hajj?, and how are the efforts to manage the Hajj f inances based on good governance?. This research is library research, using a normative juridical method with a statutory approach. Some of the findings in this study indicate that regulations in the financial management of Hajj provide a polemic of its own so that it loses its identity and principle. Dualism of authority, inefficient management, and the potential for fraud are demands to fix the messy financial management of Hajj, towards good governance-based Hajj financial management.